Estudio de prefactibilidad para la instalación de una fábrica de bolsas biodegradables a base de ácido poliláctico (PLA) - Brousset Garcia Arata, Shadia Loretta (2020)
The purpose of the present investigation is to determine the prefeasiblity of the implementation of a biodegradable bags based on PLA (polilatic acid) factory. Resarch performed in an investigation market showed a niche inside social-economical levels A and B with growth potential through which the proposed product can be developed. The location of the production plant, in Carmen De la Legua Reynoso’s district, in the department of Lima, was determined through the study of macro and microlocations. The production plant size was evaluated through 4 criteria: market, productive resources, technology and breakeven. Market being the limiting criteria, thus the plant size of 8,339 boxes of 100 rrolls of 50 biodegradable bags. The initial investment for this project, which includes tangible and intangible goods, was estimated at 3,991,637 peruvian soles. Through an economic and financial assessment, the following values were obtained: Economic NPV 3,359,510 peruvian soles, Economic IRR 40%, financial NPV 3,545,020 peruvian soles and finantial IRR 54%, which concludes that the project is viable.